Blended Humor and Mind Mapping in Improving 21st Century Skills - Anggraeni, Anastasia Dewi (Universitas Negeri Malang, 2019)
Instructional communication that occurs in the classroom is expected to be pleasant communication for achieving instructional goals and improving 21st century skills. 21 st Century skills include communication, collaboration, critical thinking, and creativity. This study aims to enhance students’ 21st century skills through the application of humor and mind mapping in classroom instructional activities. The object in this study was the 65 freshman in the Professional Education Department of Universitas Indraprasta PGRI. The method used in this research was descriptive qualitative. The results show that learning in the classroom becomes more fun and stress free to understand through humor applied through humorous, motivating, and ice breaking videos. Besides, there are communications between students through discussion forums and collaboration between them in the learning process. Other than that, student cognitive in critical thinking about the problems discussed in the learning material improves, as well as their creativity in organizing learning media digitally and non digitally.